A systematic review of risks associated with environmental change on refractive and non-refractive ocular health: Special focus on Africa - Emmanuel Elochukwu Okenwa-Vincent; Nathan Riel; Linda S. Pagani (Hygiene and Environmental Health Advances)
Background: Over the past two decades, the African continent has faced numerous environmental shifts that affect population health. Climate change, rapid urbanization, and air pollution contribute significant risks to human health. The impact of these shifts on refractive and non-refractive ocular health in Africa remains largely empirically undocumented. Objectives: A systematic review of the risks associated with environmental factors on refractive and non-refractive ocular health, with a specific emphasis on the African context. Methods: This systematic review over the recent decade, conforming to PRISMA guidelines, spanned two primary databases, PubMed, and Google Scholar. It included a combination of keywords related to ocular health, environmental change, air pollution, climate change, water quality, and other related concepts. In total, it captured 77 articles from 2013 to July 2023 that met review quality guidelines. Results: The review comprised varied study designs with a notable inclusion of cross-sectional (25·9%), cohort (14·3%), and review articles (36·4%). Findings indicated a significant correlation between air pollutants like PM2·5 and NOx with ocular diseases such as dry eye and ocular surface disorders (16·8%), conjunctival disorders (7·8%), and myopia (5·2%). Climate change exacerbated by rising temperatures and UV radiation was implicated in 39% of studies, with a specific focus on its relation to cataracts (5·2%) and retinal-related disorders (10·4%). Additionally, indoor air pollution disproportionately affected women and children in rural settings of Africa. Conclusions: The data indicate the need for urgent continental and regional policies against air pollution and climate change to safeguard ocular health, especially among vulnerable African populations. The review underscores the need for interdisciplinary policy to address challenges. The documentation of the relationship between environmental factors and ocular health intersects with Sustainable Development Goals that emphasize the need for improved preventive eye care and intervention, particularly among vulnerable populations and rural inhabitants.